2006
DOI: 10.1109/tvcg.2006.28
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic tactile display with thin film slider and its application to tactile telepresentation systems

Abstract: A new electrostatic tactile display is proposed to realize compact tactile display devices that can be incorporated with virtual reality systems. The tactile display of this study consists of a thin conductive film slider with stator electrodes that excite electrostatic forces. Users of the device experience tactile texture sensations by moving the slider with their fingers. The display operates by applying two-phase cyclic voltage patterns to the electrodes. The display is incorporated into a tactile telepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 18 publications
0
60
0
6
Order By: Relevance
“…A more recently introduced technique is to modulate the friction force between the finger and a mechanically grounded active surface. The friction force modulation can be achieved, for instance, by electrostatic fields [26], ultrasonic amplitude modulation [27], surface acoustic waves [28] or with the squeezed film effect [29], [30].…”
Section: Roughness and Texture In Manufacturing And Virtual Realitymentioning
confidence: 99%
“…A more recently introduced technique is to modulate the friction force between the finger and a mechanically grounded active surface. The friction force modulation can be achieved, for instance, by electrostatic fields [26], ultrasonic amplitude modulation [27], surface acoustic waves [28] or with the squeezed film effect [29], [30].…”
Section: Roughness and Texture In Manufacturing And Virtual Realitymentioning
confidence: 99%
“…The behavior of interdigital electrodes in the context of electroadhesion has recently been studied extensively [8,11,12]. Electroadhesion has also been applied to surface haptic displays [13][14][15][16][17][18], in which electroadhesion modulates friction on a transparent electrode that covers an LCD surface, to create haptic effects. In those haptic applications, planar electrodes have been preferred, rather than inter-digital electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies in the field of haptics reported that their electroadhesion force decreases under a constant DC voltage applications [13,16,22]. In those studies, less conductive materials are used as surface insulators, whereas electrostatic chucks intentionally add some conductivity to the insulating materials.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed that the sensitivity of the subjects to the positive pulses was less than that of the negative or biphasic pulses. Yamamato et al [3] developed a telepresentation system for tactile exploration of remote surface textures. This system was made of two parts: a tactile sensor on the slave site and a tactile display utilizing an electrostatic actuator on the master site.…”
Section: Introductionmentioning
confidence: 99%